More than sound: signed instrumental music for deaf people (Tabanque. Revista Pedagógica, 2018)
Deaf people are one of the groups that show the least interest in music because its auditory component has been historically highlighted. However, recent research is interested in music as a multimodal phenomenon. This possibility allows to make music accessible to deaf people. In this article several music projects for/with deaf people are addressed and the possibilities of musical interpretation in sign language of pure instrumental music are analyzed.
Keywords: Music in Signed Language; cognitive metaphor; instrumental music; music projects for deaf